Strategi Promosi Produk dan Meningkatkan Penjualan melalui E- commerce pada Vapemu Store - Dharmawan, Nickra Varel; Fauzan, Ahmad; Putra, Ramdani Bayu (CV. ITTC INDONESIA, 2025)
This report presents the findings from the fieldwork conducted at Vapemu Store, focusing on promotional strategies and sales enhancement through e-commerce. The practical work experience provided valuable insights into the significance of innovation in product development and marketing strategies. The team emphasized the importance of introducing new product variants and actively listening to customer feedback, which has proven essential for expanding productivity and market share The project involved effective external communication, serving as a bridge between the fieldwork team, partners, supervising lecturers, and the university institution. A detailed budget was prepared for promotional materials, including banners and souvenirs, to support the marketing efforts The team aimed to motivate Vapemu Store to continue its growth trajectory, improve sales outcomes, and attract a larger consumer base in the future. Recommendations for ongoing development were also provided, highlighting the need for continuous innovation and adaptation to market demands The procedural framework for the project included regular coordination meetings among the fieldwork team, ensuring that activities were well-organized and timely. The report concludes with reflections on the practical experience gained, emphasizing the importance of bridging academic knowledge with real-world business applications Overall, this fieldwork experience not only contributed to the operational success of Vapemu Store but also enriched the students' understanding of practical business dynamics, thereby fulfilling the educational objectives of the internship program.